Multi-platform practices among digital patronage creators. (October 2022) - Hair, Lee; Bonifacio, Ross; Wohn, Donghee Yvette
Digital patronage is an emergent revenue model in which fans provide recurring financial support to a content creator, as exemplified through platforms like Twitch and Patreon. Whereas previous research has investigated creator-supporter relationships, the current study investigates creators' multi-platform practices through in-depth interviews. We build on trends in creative labor studies and communication to examine how creators perceive Patreon and integrate it into their existing workflow. This study's findings contribute to a better understanding of the role of digital patronage within the broader ecosystem of creative labor platforms.